Sustainable financial institution in Indonesia: An empirical analysis of social-cultural context, nepotism, and moral hazard on the shaping of non-performing loans - Tia Rahmania; Septantri Shinta Wulandari; Asep Marfu (Sustainable Futures)
This study investigates the complex relationships among social and cultural contexts, nepotism, moral hazard, and non-performing loans (NPLs) within Indonesian financial institutions. Using survey data from a sample of these institutions, it employs structural equation modeling (SEM) to analyze these relationships. The findings reveal significant paths: social context significantly influences nepotism (β = 0.345 or 34.5%) and moral hazard (β = 0.347 or 34.7%), while cultural context has notable effects on nepotism (β = 0.157 or 15.7%) and NPLs (β = 0.379 or 37.9%). Nepotism (β = 0.168 or 16.8%) and moral hazard (β = 0.325 or 32.5%) also directly impact NPLs, highlighting their roles as mediators between social and cultural contexts and loan portfolio quality. These results underscore the pivotal roles of these factors in shaping organizational behavior and risk management practices. The study provides critical insights for practitioners, policymakers, and scholars focused on enhancing the sustainability and integrity of financial institutions in Indonesia. However, its reliance on cross-sectional data and self-reported surveys, and the focus solely on Indonesian institutions, may affect the generalizability of the findings. Despite these limitations, the study underscores the importance of addressing issues like nepotism and moral hazard to improve financial stability in the region.